Psychogenic Polydipsia: The Result, or Cause of, Deteriorating Psychotic Symptoms? A Case Report of the Consequences of Water Intoxication - Melissa Gill; MacDara McCauley (Case Reports in Psychiatry)
Water intoxication is a rare condition characterised by overconsumption of water. It can occur in athletes engaging in endurance sports, users of MDMA (ecstasy), and patients receiving total parenteral nutrition. This case outlines water intoxication in a patient with psychogenic polydipsia. When the kidney’s capacity to compensate for exaggerated water intake is exceeded, hypotonic hyperhydration results. Consequences can involve headaches, behavioural changes, muscular weakness, twitching, vomiting, confusion, irritability, drowsiness, and seizures. Cerebral oedema can lead to brain damage and eventual death. In this case, psychogenic polydipsia led to significant hyponatraemia, cerebral oedema, and tonic-clonic seizures. Differential diagnoses for hyponatraemia are outlined. The aetiology of psychogenic polydipsia is uncertain, but postulated hypotheses are explored. Psychogenic polydipsia occurs in up 20% of psychiatric patients and this case serves to remind us to be cognizant of water overconsumption.